Analisis Kompetensi Pedagogik Guru dalam Pembelajaran Siswa Kelas IV Sekolah Dasar - Ladjamba, Sepliwan; Tuerah, Roos M.S.; Tumurang, Hetty J.; Pangkey, Richad D. H. (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to determine the competence of teachers in learning at SD Inpres Pungkol, South Minahasa Regency. This type of research is descriptive qualitative research. The research sources are the principal, teachers, and students as informants to find out the extent of teachers' pedagogical competence in learning. in class IV of SD Inpres Pungkol. Data collection techniques are observation, interviews and documentation. Data analysis techniques are based on Miles and Huberman's theory with a sequence of steps, namely data reduction, data presentation, drawing conclusions. Data validity is carried out through triangulation of sources, techniques and time. The results of the research show that the teacher's pedagogical competence in learning in class IV of SD Inpres Pungkol is very good, it can be seen that when in the learning process the teacher can master the learning process, knows the characteristics of children well, is able to arrange administration in the class such as teaching modules, ATP, CP, to the preparation of questions and evaluation of assessments as well as being able to use electronic media in learning.